Bounce back from adversity: a narrative review and perspective on the formation and consequences of athlete resilience - Mei, Zhengyang; Cai, Chenyi; Wang, Tingfeng; Lam, Chifong; He, Ranran; Luo, Shi (Frontiers in Psychology, 2025)
In the field of sports, athletes are often exposed to sports adversity or stressful situations. Athlete resilience, as a key psychological factor, is directly associated with athletes’ physical and mental health and sports performance. Despite the growing attention to athlete resilience research, the field still lacks a unified conceptual and theoretical framework to explain the formation and consequences of athlete resilience. These limitations hinder the effective translation of research findings into intervention practices. Reviewing the previous research, this study aimed to provide a narrative review of the definition, structural dimensions, and measurement methods of athlete resilience, and elucidate and analyze its formation, consequences, and synergistic interaction with sports organizational resilience on the basis of theoretical models and relevant theories. Athlete resilience refers to the capacity of athletes to evaluate and regulate their thoughts, emotions, and behaviors in response to sports adversity, thereby enhancing their potential, emotional well-being, and overall health. As a complex multifactorial structure, athlete resilience primarily covers five structural dimensions: sports motivation, self-efficacy, coping strategy, optimism, and hope. At present, the formation of athlete resilience has primarily been studied through frameworks such as the dual-pathway model, meta-model, and psychological immunity-psychological elasticity model, along with their relevant theories. Furthermore, the consequences of athlete resilience are closely associated with various psychological states and behavioral patterns athletes experience during training and competition, the most common of which include perceived stress, competition anxiety, and athlete burnout, and its mechanism can be explained by the meta-model of stress, emotions and performance. Finally, the synergistic development of athlete resilience and sports organizational resilience is crucial, as it effectively enhances the overall ability of athletes and their organizations to cope with and overcome adversity and stress. While existing research has made notable contributions to the understanding of athlete resilience, the field still lacks a more comprehensive and systematic theoretical framework to guide related research. The conceptual foundations, formation and consequences of athlete resilience, along with its synergistic interaction with sports organizational resilience, require further validation and support. This is particularly crucial for enhancing athletes’ overall well-being and their sports performance.